2022
DOI: 10.1021/acs.analchem.2c00428
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Activity Monitoring and Natural Anti-neurological Disease Drug Screening via Rational Design of Deep Eutectic Solvents and CeO2-Co(OH)2 Nanosheets

Abstract: The activity monitoring of acetylcholinesterase (AChE) and the screening of its inhibitors are critical for the diagnosis and therapy of neurological diseases. Herein, CeO2-Co­(OH)2 nanosheets were synthesized for the first time in a newly designed deep eutectic solvent (DES) composed of l-proline and Ce­(NO3)3·6H2O, and a colorimetric assay was developed for quantitative detection of AChE and anti-neurological disease drug screening. Impressively, CeO2-Co­(OH)2 composites prepared in DESs have more prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 50 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…The longer the arrow is, the greater the contribution of a variable to PC. Therefore, 12 common peaks (1,2,3,4,5,6,8,9,11,12,14,15) were used for the subsequent correlation analysis between chemical components and efficacy.…”
Section: 51mentioning
confidence: 99%
See 2 more Smart Citations
“…The longer the arrow is, the greater the contribution of a variable to PC. Therefore, 12 common peaks (1,2,3,4,5,6,8,9,11,12,14,15) were used for the subsequent correlation analysis between chemical components and efficacy.…”
Section: 51mentioning
confidence: 99%
“…Traditional Chinese medicines (TCMs) or plant-derived compounds have shown multitargeting ability in treating AD. It has been reported that Zanthoxylum nitidum [4], Scutellaria baicalensis [5], and Coptis chinensis [6] exhibit significant inhibitory effects on acetylcholinesterase (AChE) and strong antioxidant activities, becoming great potential protectors of the cholinergic system. Therefore, screening active compounds from TCMs is an important avenue to develop new drugs for multitarget therapy for AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPR can catalyze the oxidation reaction between H 2 O 2 and the substrate. [18][19][20] The common substrates are 3,3′,5,5′-tetramethylbenzidine (TMB), O-phenylenediamine (OPD) and 2,2′-acridine bis(3-ethylbenzothiazolin-6-sulfonic acid) (ABTS). After oxidation, the solution color would become blue, yellow and green, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6 AChE has become a vital biomarker and drug target in clinical diagnosis and detoxification therapy. Thus, the accurate assaying of AChE activity is highly significant from the clinical point of view, and various analytical methods have been established for this purpose, including Ellman's colorimetric, 7,8 chemiluminescent 9,10 and electrochemical approaches. 11,12 The treatment of real biological samples, however, is always highly challenging due to the interference from biomolecules and the instability of reagents.…”
mentioning
confidence: 99%